In situ selective laser gas nitriding for composite TiN/Ti-6Al-4V fabrication via laser powder bed fusion. (15th May 2020) - Morton, P.A.; Taylor, H.C.; Murr, L.E.; Delgado, O.G.; Terrazas, C.A.; Wicker, R.B.
Abstract: Laser-assisted gas nitriding of selective Ti-6Al-4 V surfaces has been achieved during laser powder bed fusion fabrication by exchanging the argon build gas environment with nitrogen. Systematic variation of processing parameters allowed microdendritic TiN surface coatings to be formed having thicknesses ranging from a few tens of microns to several hundred microns, with TiN dendrite microstructure volume fractions ranging from 0.6 to 0.75; and corresponding Vickers microindentation hardness values ranging from ∼ 7.5 GPa–9.5 GPa. Embedded TiN hard layers ranging from 50 μm to 150 μm thick were also fabricated in the laser-beam additively manufactured Ti-6Al-4 V alloy producing prototype, hybrid, planar composites having alternating, ductile Ti-6Al-4 V layers with a hardness of ∼ 4.5 GPa and a stiff, TiN layer with a hardness of ∼8.5 GPa. The results demonstrate prospects for fabricating novel, additively manufactured components having selective, hard, wear and corrosion resistant coatings along with periodic, planar or complex metal matrix composite regimes exhibiting superior toughness and related mechanical properties.